ANALYSIS OF SUSTAINABLE DEVELOPMENT IMPLEMENTATION IN SAUDI VISION 2030 POLICY - Purba, Natanael Novembri; Putri, Penny Kurnia; Nugraha, Anak Agung Bagus Surya Widya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2024)
This study aims to explain and explore how Sauid Arabia implement Saudi Vision 2030 through concept of sustainable development, Saudi Vision 2030 is a long-term development strategy unveiled by Crown Prince Muhammad Bin Salman Al-Saud. Saudi Vision 2030 policy is the government's hope as a solution to overcome various national problems that have been hampering and threatening the country's sustainability, especially after the decline in world oil prices in 2013-2015. There are three important factor that are the focus of Saudi Vision 2030 , namely economic, social and environmental. This research shows that focus on these three aspects can explain how the Saudi Vision 2030 will encourage positive changes that support sustainability and stability of Saudi Arabia after the decline in world oil prices. The results of this paper will describe and explain how the results of the implementation of the Saudi Vision 2030 policy strongly support progress on three aspects of sustainable development according to Torodov and Marinoya and carried out through liberalization efforts which have a long-term positive impact on the sustainability and stability of Saudi Arabia.